Superman, son of Kal-El - Taylor, Tom 1978-; Timms, John; Di Nicuolo, Daniele 1987- (DC Comics, 2022)
"Jonathan Kent has his own ideas about Superman's role in the world. When his father leaves Earth, the son of Superman and Lois Lane steps in to his father's large boots and dons the symbol of hope embodying everything the Man of Steel stands for -- and then some. The new Superman strives to be a more proactive champion for real change and social justice in the world. In the process, he makes some powerful enemies."
"Superman created by Jerry Siegel and Joe Shuster, by special arrangement with the Jerry Siegel family
Keywords: Superboy -- Fiktive Gestalt; Comic